Self-Regulation - Khan, Steven (Daily Express, 2007)
This article argues that self-regulation (SR) is an important concept for educators, and that the development of SR is critical to fostering the lifelong learning skills that are a desired essential learning outcome in all modern educational systems
Keywords: Self-regulated learning; Learning processes